Isolated p.H62L mutation in the CYP21A2 gene in a simple virilizing 21-hydroxylase deficient patient - Taboas, Melisa Ivana (2013)
Congenital adrenal hyperplasia due to 21-hydroxylase deficiency accounts for 90%?95% of cases.This autosomal recessive disorder has a broad spectrum of clinical forms, ranging from severe or classical, which includes the salt-wasting and simple virilizing forms, to themild late onset or nonclassical form.Most of the disease-causingmutations described are likely to be the consequence of nonhomologous recombination or gene conversion events between the active CYP21A2 gene and its homologous CYP21A1P pseudogene. Nevertheless, an increasing number of naturally occurring mutations have been found. The change p.H62L is one of the most frequent rare mutations of the CYP21A2 gene. It was suggested that the p.H62L represents a mild mutation that maybe responsible for a more severe enzymatic impairment when presented with another mild mutation on the same allele. In this report, a 20-year-old woman carrying an isolated p.H62L mutation in compound heterozygosity with c.283-13A/C>G mutation is described. Although amildly nonclassical phenotype was expected, clinical signs and hormonal profile of the patient are consistentwith a more severe simple virilizing form of 21-hydroxylase deficiency.The study of genotype-phenotype correlation in additional patients would help in defining the role of p.H62L in disease manifestation.